Analisis Faktor-Faktor Yang Mempengaruhi Kepatuhan Wajib Pajak Dalam Membayar Pajak Kendaraan Bermotor Di Kabupaten Timor Tengah Utara - Tpoi, Elisabeth Hedwiga (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
This study aims to (1) to determine the influence of taxpayer awareness on taxpayer compliance, (2) to determine the influence of service quality on taxpayer compliance, (3) to determine the effect of tax sanctions on taxpayer compliance, (4) to determine the influence of taxpayer awareness, service quality and tax sanctions on taxpayer compliance. This study uses a quantitative method. The data collection carried out in this study was by distributing questionnaires. The data analysis technique used in this study is the multiple linear regression technique. The results of the research and the results of data analysis show that: (1) Taxpayer awareness affects taxpayer compliance with the comparison of tcal and ttable values (3,949 Ëƒ 1,660) and a significance value of 0.000 Ë‚ 0.005; (2) service quality affects taxpayer compliance by comparing the value of tcal and ttable (2,353 Ëƒ 1,660) and the significance value of 0.021 Ë‚ 0.005 ; (3) Tax sanctions do not affect taxpayer compliance with the comparison of tcal and ttable values (1,144 Ë‚1,660) and a significance value of 0.256 Ëƒ 0.005; (4) Taxpayer awareness, service quality and tax sanctions simultaneously affect taxpayer compliance with the comparison of Fcal and Ftables values (23.809 Ëƒ 2.70) and significance values of 0.000 Ë‚ 0.005.